Antiviral Agents From Fungi: Diversity, Mechanisms and Potential Applications - Linnakoski, Riikka; Reshamwala, Dhanik; Veteli, Pyry; Cortina-Escribano, Marta; Vanhanen, Henri; Marjomäki, Varpu (Frontiers in Microbiology, 2018)
Viral infections are amongst the most common diseases affecting people worldwide. New viruses emerge all the time and presently we have limited number of vaccines and only few antivirals to combat viral diseases. Fungi represent a vast source of bioactive molecules, which could potentially be used as antivirals in the future. Here, we have summarized the current knowledge of fungi as producers of antiviral compounds and discuss their potential applications. In particular, we have investigated how the antiviral action has been assessed and what is known about the molecular mechanisms and actual targets. Furthermore, we highlight the importance of accurate fungal species identification on antiviral and other natural products studies.